If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x(5x + 10) = 7x Reorder the terms: 7x(10 + 5x) = 7x (10 * 7x + 5x * 7x) = 7x (70x + 35x2) = 7x Solving 70x + 35x2 = 7x Solving for variable 'x'. Reorder the terms: 70x + -7x + 35x2 = 7x + -7x Combine like terms: 70x + -7x = 63x 63x + 35x2 = 7x + -7x Combine like terms: 7x + -7x = 0 63x + 35x2 = 0 Factor out the Greatest Common Factor (GCF), '7x'. 7x(9 + 5x) = 0 Ignore the factor 7.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(9 + 5x)' equal to zero and attempt to solve: Simplifying 9 + 5x = 0 Solving 9 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 0 + -9 5x = 0 + -9 Combine like terms: 0 + -9 = -9 5x = -9 Divide each side by '5'. x = -1.8 Simplifying x = -1.8Solution
x = {0, -1.8}
| 4(4-4k)=-10-16 | | 16x-8=36 | | 1x+-4+2x=14 | | 10v-3-v=0 | | -2t^2+8t+1=0 | | -5t+7=11+-25 | | 4x+x+5=54 | | 8x^2y+8y=2x | | -9k+10-8k=0 | | -.250y+2=0 | | 180=(7x-3)(12x-7) | | 7-6x=-23 | | 2x-9=1-3x | | 5(x+10)=7x | | -8x+3(x-7)=-36 | | 8.5x+1.1=2.5x+2.25 | | -7-3x=4 | | 4(2x+6)=72 | | -4x-11=3x+10 | | 3(y^2-y+1)= | | -2x-5x=21 | | 4v^2+13v+5=-5 | | 12x-10=-2+12 | | -5v-8-10-8v=0 | | 5x+7+22=EF | | 16y-10=10y-5 | | (x-6)(x+5)=12 | | 18-(-f)=101 | | 10x=0.3-9.1 | | 28m-32x=92 | | -8-3x=16 | | -6/5=-6/5n |